2013
DOI: 10.1590/s0100-55022013000100016
|View full text |Cite
|
Sign up to set email alerts
|

Jogos para capacitação de profissionais de saúde na atenção à violência de gênero

Abstract: I PALAVRAS-CHAVE:-Violência contra a Mulher;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
0
7
0
12
Order By: Relevance
“…1 It is known that this kind of violence can result in physical, mental and emotional health problems in women, as well as entailing high economic costs for a country, either through medical expenses due to the impossibility of productive work or the consequences related to mental health.2 Violence against women is considered a priority in the human rights area, and it can occur in various forms, such as physical, psychological, moral, property or sexual violence and in 70% of the cases the perpetrator is someone with whom she either maintains or has maintained an affective bond. [1][2][3] In Brazil, according to data from the Specialized Attendance Police Stations for Women, about 205,000 women have been reported within a single year. 3 Data from the Notification of Injury Information System showed that 223,796 cases were reported for victims of domestic violence, sexual violence and others violence cases in 2015, where two out of those three cases (147,691 total) were women subjects, and they demanded care in a health unit due to violence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It is known that this kind of violence can result in physical, mental and emotional health problems in women, as well as entailing high economic costs for a country, either through medical expenses due to the impossibility of productive work or the consequences related to mental health.2 Violence against women is considered a priority in the human rights area, and it can occur in various forms, such as physical, psychological, moral, property or sexual violence and in 70% of the cases the perpetrator is someone with whom she either maintains or has maintained an affective bond. [1][2][3] In Brazil, according to data from the Specialized Attendance Police Stations for Women, about 205,000 women have been reported within a single year. 3 Data from the Notification of Injury Information System showed that 223,796 cases were reported for victims of domestic violence, sexual violence and others violence cases in 2015, where two out of those three cases (147,691 total) were women subjects, and they demanded care in a health unit due to violence.…”
Section: Introductionmentioning
confidence: 99%
“…Such thinking, "strong man and weak woman" has been historically constructed and employed to legitimize the violence perpetrated against women. 2 Studies indicate that women who have suffered violence are more likely to seek care in health services, even if they do not disclose the situation of violence experienced. The Primary Care Units being are a potential entrance gateway (through reference routes) to specialized services in violence against women (if there is any), or even for other services that the woman demands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse fenômeno apresenta diferentes níveis de severidade [1][2][3] e configura--se como um grave problema de saúde pública, devido à DOI: http://dx.doi.org/10.12957/reuerj.2017.23648 sua magnitude, gravidade, recorrência e consequências negativas sobre a qualidade de vida das vítimas [1][2][3][4][5] . Mulheres em situação de violência frequentam com assiduidade os serviços de saúde, principalmente os voltados para a atenção primária .…”
Section: Introductionunclassified
“…Cada vez mais se recorre ao uso de mídias e interfaces digitais para variadas finalidades como trabalho, relacionamento pessoal, aprendizado e diversão (ALMEIDA; SILVA; MACHADO, 2013 …”
Section: Os Serious Games Como Ferramenta De Intervenção Para a Saúdeunclassified